Sustainable Tourism Assessment in Urban Green Spaces: The Case of Khung BangKachao, Thailand - Sukhuman Klamsaengsai; Onanong Cheablam; Angsikarn Sasithornwetchakul; Watcharee Churugsa; Yeamduan Narangajavana Kaosiri (Urban Science)
Sustainable tourism planning is essential for understanding an area’s potential for sustainable development. However, the tourism sector struggles with adopting sustainable practices due to limited research on practical implementation, particularly in Thailand. Khung BangKachao, a vital green space near Bangkok, provide recreation for urban residents, but faces threats from urbanization, environmental degradation, and loss of traditional lifestyles. This study applied all four criteria and 41 indicators from the Global Sustainable Tourism Council (GSTC), a rare and rigorous approach in sustainability research that offers a model for other regions. A qualitative method was used, with content analysis based on 33 in-depth interviews and observations. Results show Category A is effective due to seasonal tourism management and legal adherence, though monitoring is weak. Category B demonstrates positive economic and social impacts. Categories C and D reveal gaps in tourism standards and environmental reporting. Tourism planning in Khung BangKachao should prioritize monitoring, community involvement, and structured management to support long-term sustainability.